Nerve Ultrasound in Traumatic and Iatrogenic Peripheral Nerve Injury - Wijntjes, Juerd (Diagnostics (Basel), 2020)
Peripheral nerve injury is a potentially debilitating disorder that occurs in an estimated 2–3% of all patients with major trauma, in a similar percentage of medical procedures. The workup of these injuries has traditionally been clinical, combined with electrodiagnostic testing. However, this has limitations, especially in the acute phase of the trauma or lack of any recovery, when it is very important to determine nerve continuity and perform surgical exploration and repair in the case of the complete transection or intraneural fibrosis. Ultrasound can help in those situations. It is a versatile imaging technique with a high sensitivity of 93% for detecting focal nerve lesions. Ultrasound can assess the structural integrity of the nerve, neuroma formation and other surrounding abnormalities of bone or foreign bodies impeding the nerve. In addition, this can help to prevent iatrogenic nerve injury by marking the nerve before the procedure. This narrative review gives an overview of why and how nerve ultrasound can play a role in the detection, management and prevention of peripheral nerve injury.